Evaluation of health-related quality of life in a physically active senior population - Fontes, Ana Paula (2022)
Background: Physical activity (PA) is a strong determinant of health and one of the most important predictors of healthy aging and health-related quality of life (HRQoL). The aim of the study was to understand the HRQoL of a senior population practicing PA and its association with some socio-demographic characteristics, the levels of PA, and functional independence. Methods: This is a correlational study with a sample of 376 individuals of both sexes. The data collection instruments were a socio-demographic and health questionnaire, the international PA questionnaire (IPAQ)-short version, the Katz index, the Lawton and Brody index, and the WHOQOL-OLD and WHOQOL-BREF questionnaires. Results: The sample revealed a good perception of HRQoL, especially in the “psychological” and “social relations” domains. Sex showed a greater association with quality of life (QoL) than age. Multiple linear regression revealed that the variables with the most significant influence on the individuals’ QoL were related to health (“Presence of chronic disease” and “habitual use of medication”). The QoL related to "social relationships" is the domain with more predictors, with a markedly socio-demographic focus. Conclusions: Practicing PA proved to be a HRQoL predictor, where “sensory function” and HRQoL related to “social relations” are included. Despite PA practice and socio-demographic characteristics being able to predict some HRQoL domains, health-related variables showed a more robust presence in this prediction.